Influence of organizational culture, job satisfaction and work experience on employee work motivation regional secretariat financial section sungai penuh city - Wazirman Wazirman; Amalia Nada Fitri; Apridanzah Pratama; Candra Abrianto; Dora Butar-butar (Education and Social Sciences Review, 2022)
This study aims to see the effect of (1) Organizational culture on employee motivation in the Finance Division of the Sungai Penuh City Regional Secretariat (2) Job satisfaction on the work motivation of employees of the Regional Secretariat of the Regional Secretariat of Sungai Penuh (3) Work experience on the work motivation of employees of the Finance Section of the Regional Secretariat of Sungai Penuh City(4)Organizational culture, job satisfaction and work experience have a joint effect on the work motivation of employees of the Regional Secretariat of Sungai Penuh City. The population in this study were all employees Sungai penuh City Regional Secretariat Finance Sectionas many as 31 people. The technique of determining the number of samples using total sampling. The data analysis technique used multiple regression by fulfilling the requirements of the classical assumption test of normality, and multicollinearity, heteroscedasticity. The results of this study indicate that (1) Organizational culturehas a positive significant effect on employee motivation in the Finance Division of the Sungai Penuh City Regional Secretariat (2) Job satisfactiongive a positive influence on the work motivation of the employees of the Regional Secretariat of the Finance Division of Sungai Penuh City (3) Work experienceprovide a positive influence on the work motivation of employees of the Regional Secretariat of the Finance Division of Sungai Penuh City (4) Organizational culture, job satisfaction and work experiencecollectively have a positive effect on the work motivation of the employees of the Regional Secretariat of the City of Sungai Penuh.